Exploring the Interpersonal Meaning in two extracts from Chimamanda Ngozi Adichie’s Purple Hibiscus and Chinua Achebe’s Anthills of the Savannah : A Comparative Systemic Functional Linguistic Perspective. - YOKOSSI, Tchorkpa Daniel (My University, 2018)
ABSTRACT: This paper examines Mood Patterns in some passages from Adichie’s Purple Hibiscus and Achebe’s Anthills of the Savannah. More specifically, two extracts from the above mentioned prose fiction have been purposefully selected, described and analyzed from the Systemic Functional Linguistics perspective in order to reveal how the lexicogrammatical features of the interpersonal meaning of the studied extracts underpin the perception of the two authors throughout their novels. The article goes further and highlights the similarities and differences in the interpersonal functions of the extracts under scrutiny in terms of their contents and how the English language has been used therein to construe the above pinpointed authors’ world views of the issues dealt with in their writings. The findings of the study have, among others, revealed that the gap between Achebe’s and Adichie’s writings is not full size and that the former has actually paved the way to the latter.
Keywords: Keywords: Interpersonal Meaning; Sytemic Functional Linguistics; Mood Patterns; Mood types; Modality; Adjuncts.